2015
DOI: 10.1007/s11104-015-2694-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Australian wheat genotypes for response to variable nitrogen application

Abstract: Aims The key aim was to assess the genetic variation for nitrogen (N) response and stability in spring wheat germplasm to determine the scope for improvement of nitrogen use efficiency (NUE) under water-limited, low yielding conditions. A further aim was to evaluate NUE stability and NUE-protein yield (PY) as suitable NUErelated traits for selection. Methods The traits measured included grain yield (GY, kg ha) and NUE (kg GY kg −1 N) under varying N applications at all sites, and NUE for protein yield (NUE-PY)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 36 publications
8
30
0
Order By: Relevance
“…Generally, wheat lines that expressed the highest mean grain yields in each study were also among the most stable within each of the three studies. Similar findings were reported in a panel of 25 spring barley ( Hordeum vulgare L.) varieties by Anbessa et al () and eight wheat lines by Mahjourimajd et al () who reported that the most stable lines generally experienced lower grain yield reduction between high‐ and low‐N conditions than did the least stable lines. The present investigation also found significant variation in the adaptability of wheat lines over and within specific N environments, indicating the existence of genotypic variation in broad vs. specific adaptability to both favorable and unfavorable environments.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Generally, wheat lines that expressed the highest mean grain yields in each study were also among the most stable within each of the three studies. Similar findings were reported in a panel of 25 spring barley ( Hordeum vulgare L.) varieties by Anbessa et al () and eight wheat lines by Mahjourimajd et al () who reported that the most stable lines generally experienced lower grain yield reduction between high‐ and low‐N conditions than did the least stable lines. The present investigation also found significant variation in the adaptability of wheat lines over and within specific N environments, indicating the existence of genotypic variation in broad vs. specific adaptability to both favorable and unfavorable environments.…”
Section: Discussionsupporting
confidence: 86%
“…Generally, wheat lines that expressed the highest mean grain yields in each study were also among the most stable within each of the three studies. Similar findings were reported in a panel of 25 spring barley (Hordeum vulgare L.) varieties by Anbessa et al (2009) and eight wheat lines by Mahjourimajd et al (2016) who reported that the most stable lines generally experienced Crop Science T A B L E 9 Correlation matrix for phenotypic traits in Study III at two N rates over six environments. Grain yield, grain protein yield (GPY), aboveground biomass (AGBM), harvest index (HI), grain N concentration (GNC), N uptake efficiency (NUpE) lower grain yield reduction between high-and low-N conditions than did the least stable lines.…”
Section: Genotypic Variation For Nue In Elite Germplasmsupporting
confidence: 76%
See 1 more Smart Citation
“…RAC875 (RAC655/3/ Sr21/4*LANCE//4*BAYONET) is high-yielding in the drought and heat-prone South Australian environments (Izanloo et al 2008;Bennett et al 2012). Mace (WYALK-ATCHEM/STYLET//WYALKATCHEM) was bred and released by Australian Grain Technologies (AGT) in 2008 and preliminary studies suggest that Mace has high N-use efficiency across different South Australian environments (Mahjourimajd et al 2016).…”
Section: Plant Materialsmentioning
confidence: 99%
“…However, the challenges have been the degree of phenotypic variation for this complex trait and the difficulty in getting reliable data from field trial studies (80). There are now better statistical tools for molecular mapping, and the need for more careful experimental design and replicate testing has been recognized (90,119).…”
Section: Beyond Nue: Toward the Genetics Of N-fixing Plantsmentioning
confidence: 99%